Cultivating Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (OCEAN) Personality in Madrasah Education: The Impact of Leadership, Institutional Ethos, and Teacher Role Models on Student Development - Marlina, Yuli; Qomaruzzaman, Bambang; Badrudin, Badrudin; Samsul Arifin, Bambang (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study addresses the limited research on how external factors influence student personality development within Madrasahs, focusing on the OCEAN personality dimensions: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. It examines the effects of Madrasah head leadership, institutional culture, and teacher role models on shaping these traits in students at State Islamic Senior High Schools (MAN) in DKI Jakarta. Using a quantitative approach, the research involved 337 respondents, including both teachers and students, and employed multiple linear regression analysis to test the relationships between the independent variables and student personality traits. The findings indicate that leadership, culture, and teacher behavior significantly and positively affect the development of students’ personalities. These results highlight the co-contributory role of strong leadership, inclusive school culture, and exemplary teaching behavior in fostering holistic student development. The study concludes that effective educational environments contribute not only to academic success but also to students’ emotional well-being and life skills. Notably, principals' leadership strategies were found to significantly influence students' personality development in madrasahs, suggesting that variations in leadership practices across different institutions may impact the generalizability of the findings. Consequently, the study offers recommendations for strengthening leadership and role modeling within Islamic educational institutions.